2019
DOI: 10.1111/tmi.13328
|View full text |Cite
|
Sign up to set email alerts
|

Are out‐of‐school adolescents at higher risk of adverse health outcomes? Evidence from 9 diverse settings in sub‐Saharan Africa

Abstract: objectives We analysed mutually comparable surveys on adolescent attitudes and behaviours from nine sites in seven sub-Saharan African countries, to determine the relationship between school enrolment and adolescent health outcomes.methods Data from the Africa Research, Implementation Science, and Education Network crosssectional adolescent health surveys were used to examine the associations of current school enrolment, self-reported general health and four major adolescent health domains: (i) sexual and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 74 publications
5
24
0
Order By: Relevance
“…Some of the most interesting findings from this set of surveys, among many, relate to the comparison that was made between in‐school and out‐of‐school adolescents7. As well as showing, as expected, that in‐school adolescents reported that their life was ‘going well’, the study showed that out‐of‐school adolescents were at highest risk of reporting poor general health in settings with high average levels of school enrolment.…”
supporting
confidence: 54%
“…Some of the most interesting findings from this set of surveys, among many, relate to the comparison that was made between in‐school and out‐of‐school adolescents7. As well as showing, as expected, that in‐school adolescents reported that their life was ‘going well’, the study showed that out‐of‐school adolescents were at highest risk of reporting poor general health in settings with high average levels of school enrolment.…”
supporting
confidence: 54%
“…Decreasing school dropout rate improves the sexual and reproductive health outcomes of the adolescents. 12 The study done in Uganda also revealed that out-of-school adolescents were less likely to practice safe sex and to use modern family planning methods than in-school adolescents. 13,14 Unlike the current study, previous studies conducted in different part of the country have mainly focused on inschool-adolescents who relatively have a better access to SRH service and information when compared to out-ofschool adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary schooling has been linked with sustained benefits for health, economic and social outcomes [1], including reductions in mortality [2], and reductions in the risk of cardiovascular [3, 4] and sexually transmitted diseases [5, 6]. Investment in secondary schooling may not only yield large dividends for individuals themselves–but also for other household members [7, 8].…”
Section: Introductionmentioning
confidence: 99%